2012
DOI: 10.1007/s12105-012-0352-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Dysplasia and Ploidy Status in Oral Leukoplakia

Abstract: Oral leukoplakia and other potentially malignant disorders (PMD) may progress to oral squamous cell carcinoma (OSCC). The gold standard for assessing the potential for malignant transformation remains histologic examination with the aim of grading the dysplastic changes. However, not all lesions with dysplasia will progress to OSCC. DNA ploidy has been suggested as a method to predict the clinical behaviour of PMD. This study reports on the use of high-resolution flow cytometry to determine the ploidy status o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Preneoplastic oral epithelium is usually aneuploid (8)(9)(10) and DNA aneuploidy indicates risk of malignant transformation (11). These changes can be measured using karyometry, flow cytometry (12), and image analysis (13) and more subtle loss of heterozygosity by molecular methods (14).…”
Section: Introductionmentioning
confidence: 99%
“…Preneoplastic oral epithelium is usually aneuploid (8)(9)(10) and DNA aneuploidy indicates risk of malignant transformation (11). These changes can be measured using karyometry, flow cytometry (12), and image analysis (13) and more subtle loss of heterozygosity by molecular methods (14).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, individuals with Down syndrome carrying an extra copy of chromosome 21 have a 50% lower risk of developing a solid tumor but a significantly higher risk of developing leukemia, as compared to individuals with a normal karyogram (Hasle et al, 2000). On the other hand, aneuploidy is an early event found in typical pre-cancer stages such as cervix dysplasia, Barrett esophagus, leukoplakia and bronchus dysplasia (Sandritter, 1965; Reid et al, 2000; Hanselmann and Oberringer, 2001; Lothschütz et al, 2002; van Zyl et al, 2012) liver cirrhosis (Attallaha et al, 1999) and others (Bohm and Sandritter, 1975). It is interesting that aneuploidy is even detectable in chronic inflammatory tissue such as wounds (Ermis et al, 1998; Oberringer et al, 1999) and inflammatory bronchial tissue (Hanselmann and Oberringer, 2001; Lothschütz et al, 2002), after acute and chronic hypoxic conditions (Ueyama et al, 2012; Kondoh et al, 2013), and after exposure to physical (Grosovsky et al, 1996; Kirsch-Volders et al, 1996) or chemical stressors (Galloway and Ivett, 1986; Mattiuzzo et al, 2006; Tayama et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The role of DNA aneuploidy as a potential biomarker of early oral carcinogenesis and tumour progression has been investigated by means of both image and flow cytometry with promising results, mainly addressing oral leukoplakia and lesions with dysplasia (Pentenero et al, 2009;Torres-Rendon et al, 2009;Bradley et al, 2010;Bremmer et al, 2011;Brouns et al, 2012;van Zyl et al, 2012;Sperandio et al, 2013). Several studies also addressed DNA ploidy in OLP with contrasting results: some found no occurrence at all (Rode et al, 2006;Neppelberg and Johannessen, 2007;Acha-Sagredo et al, 2011;Sperandio et al, 2013), while others reported a substantial DNA aneuploidy rate of about 27-28% (Yarom et al, 2009;Hosni et al, 2010;Chitturi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%